Comparison of the macroparasite communities of stocked and wild trout (Salmo trutta) from the West of Ireland - HOLLAND, CELIA (My University, 2002)
The aim of the present study was to compare the helminth infra and component communities of wild and stocked brown trout in Lough Feeagh, in the west of Ireland, and also to examine the establishment and development of helminth communities in stocked brown trout. Fish were sampled in May, August and November 1997 and 1998 and an additional sample of wild brown trout was examined in April 1997. In total 217 wild trout and 122 stocked trout were examined. The acanthocephalans Acanthocephalus clavula and Pomphorhynchus laevis were the first parasite species to infect stocked trout in May 1997. In May 1998 both acanthocephalan species along with the trout specialists Eubothrium crassum and Crepidostomumfarionis were the first to infect trout. Mean species richness values for stocked trout increased from May to November, in 1997 and 1998. For wild trout, mean species richness values increased from April to November, in 1997 and decreased from May to November in 1998. The parasite communities of wild trout were richer than those of stocked trout in May of both years. In August the parasite communities recorded for wild and stocked trout were similar in terms of the number of species present but differed in terms of structure, and in November the parasite communities of stocked trout were richer than those of wild trout.
PUBLISHED
Keywords: Zoology; Parasitology; Acanthocephalus clavula; Pomphorhynchus laevis; trout